Report of the third meeting of regional body secretariats network : (Food and Agriculture Organization of the United Nations, 2011)
The Third Meeting of Regional Fishery Body Secretariats Network (RSN-3) was held in Rome, from 7 to 8 February 2011. It addressed many pressing issues relating to global and regional fisheries governance, including illegal, unreported and unregulated (IUU) fishing, overcapacity, the ecosystem approach to fisheries management, small-scale and inland fisheries and the outcomes of the twenty-ninth Session of FAO Committee on Fisheries held in Rome during the previous week.